2016
DOI: 10.5433/1679-0359.2016v37n2p1069
|View full text |Cite
|
Sign up to set email alerts
|

Feed intake, nutrient digestibility, milk production and composition in dairy cows fed silage of wet brewers grain

Abstract: The aim of this study was to evaluate the supply of wet brewers grain silage with and without nutrient additives in ensiling (wheat bran, soybeans hulls and ground corn), and the effect of additives on the intake and digestibility of dry matter and nutrients as well as the efficiency, production and milk composition of Holstein cows. Four multiparous Holstein cows were used, with an average milk production of 25 liters per day. The cows were randomly assigned, via the Latin Square design (4x4), to one of four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In the current study, lambs consuming WPM -WDGS had significantly lower ADG but the overall efficiency of feed utilization was no different from that of the animals consuming WPMS + SOM and WPMS + DDGS as shown by the FCR. The complementary effect of diet components was seen to play a significant role in improving WDGS's feeding values (Souza et al, 2016) such as an increase in DM and overall nutrient composition. Comparing wet or dried DGS as a supplement in growing steers consuming alfalfa hay plus sorghum silage, Ahern et al (2016) found that there were no differences in the form in which DGS was supplemented in terms of growth performance.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the current study, lambs consuming WPM -WDGS had significantly lower ADG but the overall efficiency of feed utilization was no different from that of the animals consuming WPMS + SOM and WPMS + DDGS as shown by the FCR. The complementary effect of diet components was seen to play a significant role in improving WDGS's feeding values (Souza et al, 2016) such as an increase in DM and overall nutrient composition. Comparing wet or dried DGS as a supplement in growing steers consuming alfalfa hay plus sorghum silage, Ahern et al (2016) found that there were no differences in the form in which DGS was supplemented in terms of growth performance.…”
Section: Discussionmentioning
confidence: 98%
“…Distillers' grains with or without solubles are generally characterized by high protein, fat and neutral detergent fibre (NDF) (Akayeza et al, 1998) which can, therefore, be considered a valuable feed option for ruminants. Furthermore, they contain a higher proportion of rumen undegradable protein (RUP) and have a lower starch content compared to the source grain (Souza et al, 2016) which is particularly important to adequately meeting the nutrient needs of fast-growing or high-producing animals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite being a potentially good option for economic and quality reasons, the high moisture content of WDGS imposes storage, transport, and high perishability constraints on farmers (Anderson et al, 2015;Moyo et al, 2016;Ranathunga et al, 2018). Such consistency easily results in the formation of mold and quality decrease aft er four days under normal handling conditions (Souza et al, 2016;Moyo et al, 2016). Drying WDGS (40 -70% moisture) to produce dried distillers' grains with solubles (DDGS, 10 -13% moisture) is costly, and the heat processing during drying can make DDGS more susceptible to protein damage and lead to poor amino acid availability (Cao et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It improves the milk yield and composition and does not negatively influence blood components of dairy cows or dry matter intake ( Belibasakis & Tsirgogianni, 1996 ; Chiou et al., 1998 ). Addition of BGS as feed for lactating cows increases the fat and protein content in milk ( West, Ely & Martin, 1994 ; De Souza et al., 2016 ). BSG addition (at the level of 35%) to the lamb diet was found to exert a positive effect on their growth performance (higher body weight and daily gains).…”
Section: Applications Of Brewery By-products In the Food Industrymentioning
confidence: 99%